The biology and ecology of ticks shape the potential for the transmission of zoonotic pathogens - Agustin Estrada-Pena (Frontiers Research Topics, 2015)
Ticks are noticeable by the high diversity of pathogens they can transmit, most of them with implications in human and animal health. Ticks are arachnids, meaning that they do not share the biological and ecological features of the mosquitoes and other parasitic Diptera. The natural foci of tick-borne pathogens may be as large as a continent, or be restricted to small portions of a country, without apparently too many similar features. The life cycle of the ticks involved three developing instars. The precise relationships of ticks and their hosts, the specific seasonal pattern of activity of ticks, and the still poorly known molecular relationships between ticks and the pathogens they can transmit, make these vectors a specially fecund field of research. Importantly, extensive studies on the biological and ecological relationships of ticks and abiotic (climate and vegetation) conditions have revealed the fine-tuning of the ticks and the pathogens they transmit, together with the biological effects of host and the driving features by the climate. The studies on tick-transmitted pathogens have been on the rise in the last years. There is a growing interest in understand the somewhat complex relationships between the landscape, the climate, the vectors and the pathogens, because the concerns of spread, probably driven by subtle changes in climate and man made alterations of the landscape. Studies on Lyme borreliosis are addressing the interesting issue of the relationships between the climate, the tick activity patterns, and the selection of strains according to the reservoir availability. Furthermore, the expanding field of habitat suitability modeling has been applied with different degrees of success to evaluate and quantify the risk of disease transmission. In such exponentially growing field, revisionary books are clearly welcome additions to the bibliographical tools of researchers. It is however necessary the compilation of works devoted to explore the tip of the iceberg in the field of research. In this Research Topic, we wish to summarize and review the studies on ecology, molecular biology, and tick-host-pathogens interactions, provided to resolve the important issues of ticks and pathogens. We want not only the results obtained by newly developed molecular tools, but rigorous reviews of the most recent advances in these issues. This Topic will cover aspects of both human and animal health, with special interest on zoonoses. Aspects of the biology of the ticks, as affecting the transmission of pathogens, are of special interest in this Topic. Studies on ticks of the poorly known family Argasidae, as related to their involvement on pathogen transmission, are especially welcome. We also wish to describe the perspective of the field in the future. Finally, the presentation of ongoing original works is greatly encouraged.